English metalanguage awareness among primary school teachers in Hong Kong - Tsang, Wai Lan (Pusat Pengajian Bahasa dan Linguistik.FSSK,UKM, 2011)
With the introduction of the English Language Proficiency Assessment for Teachers in Hong Kong, local English teachers’ performance in the assessment has been in the spotlight. Among the five papers in the assessment, teachers’ scores for the writing paper, a composite of two tasks¾expository writing and error correction and explanation, have consistently recorded the lowest since the implementation. One recurrent comment is teachers’ insufficient understanding and use of metalinguistic terminology. It is against this background that the present study was conducted. It aimed to explore the extent to which local English teachers in primary schools were aware of English metalinguistic terms at different structural levels. 20 in-service primary English teachers participated in an English grammar metalanguage test, modelled on Andrews (1999), and their performance revealed three key patterns: (1) the lowest mean score in the explanation component, (2) recognition of examples of grammatical functions being much harder than that of grammatical forms, and (3) errors at the word level being more readily to be corrected and explained than those at the phrasal and clausal levels. Their performance also suggested one possible discrepancy between primary English teachers and the secondary counterparts, where the primary teachers were better at the lower level of metalanguage application (e.g., recognition of examples for metalinguistic terms) and the secondary teachers at higher-level applications (e.g., error correction). The paper concludes with a suggestion that systematic micro-metalinguistic input be integrated in teacher training courses and be used more actively among in-service teachers in their teaching context.